Intersite variability of CSF Alzheimer's disease biomarkers in clinical setting. Issue 4 (9th November 2012) - Dumurgier, Julien; Vercruysse, Olivier; Paquet, Claire; Bombois, Stéphanie; Chaulet, Chloé; Laplanche, Jean‐Louis; Peoc'h, Katell; Schraen, Susanna; Pasquier, Florence; Touchon, Jacques; Hugon, Jacques; Lehmann, Sylvain; et al.
Abstract: Background: The assessment of total tau, phosphorylated tau (pTau‐181) and amyloid beta (Aβ 1–42) concentrations in the cerebrospinal fluid (CSF) of subjects has been validated for the diagnosis of Alzheimer's disease (AD). Although these measurements have shown some variability, little is known about their intersite variability in clinical settings. Methods: A total of 880 subjects (AD, n = 515; non‐AD, n = 365) from three French memory centers were included. Receiver–operating characteristic analyses were performed to computerized area under curves (AUCs) and optimal thresholds for each biomarker in the three centers. A test–retest study was performed in a group of 32 CSF samples by repeated blind analysis of the three biomarkers using the same immunoassay batches in the three centers. Results: In the three centers, tau (AUC, 0.82–0.88) and pTau‐181 (AUC, 0.83–0.89) outperformed Aβ 1–42 (AUC, 0.70 –0.73) to discriminate subjects with AD from those without AD. An intersite variation of mean levels and cutoffs was observed for the three biomarkers. This variation was higher for Aβ 1–42 (range of cutoff, 368–582 pg/mL) than for tau (range of cutoff, 289–353 pg/mL). In a test–retest study, the mean interlaboratory coefficients of variation were 12.2% for Aβ 1–42, 11.3% for tau, and 11.5% for pTau‐181. Conclusion: Intercenter variability of CSF biomarkers has been confirmed in a multisite cohort of subjects and can be improved in clinical settings. Efforts on harmonization of procedures should be encouraged to optimize the accuracy of CSF biomarkers in AD.